Inhibition of microRNA-660-5p decreases breast cancer progression through direct targeting of TMEM41B - Valeria Villarreal-García; José Roberto Estupiñan-Jiménez; Vianey Gonzalez-Villasana; Pablo E. Vivas-Mejía; Marienid Flores-Colón; Irma Estefanía Ancira-Moreno; Patricio Adrián Zapata-Morín; Claudia Altamirano-Torres; José Manuel Vázquez-Guillen; Cristina Rodríguez-Padilla; Recep Bayraktar; Mohamed H. Rashed; et al. (Hereditas)
Abstract Background Breast cancer is the most prevalent cancer among women worldwide. Most breast cancer-related deaths result from metastasis and drug resistance. Novel therapies are imperative for targeting metastatic and drug-resistant breast cancer cells. Accumulating evidence suggests that dysregulated microRNAs (miRNAs) promote breast cancer progression, metastasis, and drug resistance. Compared with healthy breast tissue, miR-660-5p is notably overexpressed in breast cancer tumor tissues. However, the downstream effectors of miR-660-5p in breast cancer cells have not been fully elucidated. Our aim was to investigate the role of miR-660-5p in breast cancer cell proliferation, migration, invasion, and angiogenesis and to identify its potential targets. Results Our findings revealed significant upregulation of miR-660-5p in MDA-MB-231 and MCF-7 cells compared with MCF-10 A cells. Furthermore, inhibiting miR-660-5p led to notable decreases in the proliferation, migration, and invasion of breast cancer cells, as well as angiogenesis, in HUVEC cells. Through bioinformatics analysis, we identified 15 potential targets of miR-660-5p. We validated TMEM41B as a direct target of miR-660-5p via Western blot and dual-luciferase reporter assays. Conclusions Our study highlights the upregulation and involvement of miR-660-5p in breast cancer cell proliferation, migration, invasion, and angiogenesis. Additionally, we identified TMEM41B as a direct target of miR-660-5p in breast cancer cells.